The Impact of the Otago Exercise Program on Frailty and Empowerment in Older Nursing Home Residents: A Randomized Controlled Trial - Sevnaz Sahin; Fisun Şenuzun Aykar; Yasemin Yildirim; Parinaz Jahanpeyma (Annals of Geriatric Medicine and Research, 2022)
Background This study assessed the impact of Otago exercises on frailty and empowerment in older nursing home residents. Methods This randomized controlled trial included 72 individuals aged over 65 years residing in a single nursing home in Izmir, Turkey. The participants were randomly assigned to the Otago exercise group (OEG) or control group (CG). The OEG performed Otago exercises for 45 minutes, 3 days per week for 12 weeks plus a walking program the 3 other days of the week. In addition to Otago exercise training, the OEG received training based on empowerment consisting of 10 sessions lasting 30 minutes each. The CG received no intervention except routine care in the nursing home. The data collected were sociodemographic characteristics, Edmonton Frail Scale (EFS) scores, and Elderly Empowerment Scale (EES) scores before and 3 months after the intervention. Results We observed significant differences between the mean EFS (p=0.0001) and mean EES (p=0.0001) before and 3 months after the intervention in the OEG compared to the CG. We also observed a significant difference between the OEG and CG in mean EFS (p=0.018) and EES (p=0.0001) 3 months after the intervention. Conclusion The results of the present study demonstrated the positive impact of the Otago exercise program on preventing/delaying frailty and enhancing empowerment in older people.